Defining Equity Criteria for Determining Fare Zones in Integrated Passenger Transport - Denis Šipuš; Borna Abramović; Martina Jakovčić (Journal of Advanced Transportation)
Fare system models in public transport are researched based on the fact that they represent a direct and flexible instrument of influencing passenger behavior and covering public transport costs, which contributes to the sustainability of public passenger transport. Integrated passenger transport, as a concept of public transport management that uses a zonal fare system, defines transport service prices within a fare zone. An analysis of existing fare systems reveals that current systems do not offer equitable access for passengers and that the transport service is not available to everyone. To resolve the issue of the transport disadvantage of potential passengers, society and space, fare system models must be changed to provide equity for disadvantaged participants of the system. This would do away with transport and social disadvantage in the analyzed region. The aim of this research is to define equity criteria in determining fare zones in integrated passenger transport. This is a precondition for an equitable fare model which would ensure an impartial and fair charge of transport services within zones.